2020
DOI: 10.32615/ps.2019.164
|View full text |Cite
|
Sign up to set email alerts
|

Special issue in honour of Prof. Reto J. Strasser - Efficacy of botanical pesticide for rotifer extermination during the cultivation of Nannochloropsis oculata probed by chlorophyll a fluorescence transient

Abstract: Nannochloropsis is widely used in aquaculture as a feed source. However, large-scale cultivation of Nannochloropsis usually fails due to rotifer contamination. In order to identify an effective technique for reducing rotifer contamination, the effect of Brachionus plicatilis contamination on photosynthetic characteristics in Nannochloropsis oculata and the efficacy of the celangulin (CA):toosendanin (TSN) (1:9) combination for rotifer extermination were investigated using chlorophyll a fluorescence transient. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…These results suggested that excess radiation energy could not be consumed through photochemical quenching and thermal dissipation, which may lead to photoinactivation of PS II, and even photodamage. In fact, we also observed that RC/ CS was decreased by 87.0 % in chilled tomato (Table 4), which suggested that chilling stress led to the inactivation of PS II reaction centers and decreased the density of active PS II reaction centers (Zhang et al 2020c). In our present study, there was higher Y(II), qP, Y(NPQ), and NPQ, and lower Y(NO) in LTBR plants than in LT ones (Table 3).…”
Section: Discussionmentioning
confidence: 57%
“…These results suggested that excess radiation energy could not be consumed through photochemical quenching and thermal dissipation, which may lead to photoinactivation of PS II, and even photodamage. In fact, we also observed that RC/ CS was decreased by 87.0 % in chilled tomato (Table 4), which suggested that chilling stress led to the inactivation of PS II reaction centers and decreased the density of active PS II reaction centers (Zhang et al 2020c). In our present study, there was higher Y(II), qP, Y(NPQ), and NPQ, and lower Y(NO) in LTBR plants than in LT ones (Table 3).…”
Section: Discussionmentioning
confidence: 57%
“…In this study, chilling decreased Y(II) and qP by 39.3 and 18.0%, respectively (Table 1), which suggested that chilling decreased the utilization of absorbed light energy in chloroplasts by the closure of PSII. The decrease in RC/CS under chilling stress (Table 2) further indicated that chilling led to the inactivation of PSII reaction centres and decreased the density of active PSII reaction centres (Zhang et al 2020). We observed that the inhibition of AOX pathway activity caused significant decreases in Y(II), qP, and RC/CS in tomato seedlings under both normal temperature and chilling conditions (Tables 1, 2).…”
Section: Discussionmentioning
confidence: 57%
“…These insecticides attack the animals' digestive system, causing death owing to cellular damage in the midgut. Zhang et al [54] found the elevation in photosynthetic performance of Nannochloropsis cells while using the combination of celangulin and toosendanin at 1:9 ratio, which could be due to the elimination of Brachionus plicatilis (rotifer) breeding. As a result, plant-derived insecticides have the potential and feasibility to intervene in biological contaminations in microalgae and cyanobacteria mass cultures.…”
Section: Biological Control Methodsmentioning
confidence: 99%